Microbial Assisted Date Palm Nanocellulose Isolation And The Fabrication Of Hydrophobic Nanostructured Aerogel For Oil Removal - Mohamed, Elarbash Suhail Salem (2024)
The integration of biological processes, exemplified by Aspergillus niger, emerges as a cornerstone for innovative and eco-conscious practices in nanocellulose isolation. This thesis investigates the isolation of nanocellulose from date palm sheath fibers (DPSF) using Aspergillus niger, and the fabrication of hydrophobic aerogel. Pretreatment of DPSF was initially done prior to the microbial treatment, including pulping and bleaching process to get rid of lignin and other impurities. Post treatment including homogenization process was also included to effectively separate the nano fibers. The date palm sheath fibers showcased a cellulose content of 49.3%, accompanied by 22.7% lignin and 20.4% hemicellulose. Leveraging the enzymatic action of Aspergillus niger effectively dismantled the complex lignocellulosic structure, yielding nanocellulose with substantially reduced size. Extended incubation periods, notably the 96-hour treatment (DPSF-96), markedly decreased fiber size, with 81.3% ranging between 0 to 10 nm, albeit reducing the yield to 84%. Notably, DPSF- 72 exhibited optimal yield with most fibers falling within the nano-scale range (<100 nm). TEM analysis vividly displayed nanocellulose fibrillation post-microbial enzyme action, portraying individual fibers separating from bundled structures, demonstrating smaller diameters and enhanced fiber dispersion. In comparing zeta potential values, commercial nanocellulose registered -30.9 ± 4.7 mV, while the isolated variant showcased superior stability with -33.4 ± 2.7 mV.